1995
DOI: 10.1037/0033-2909.117.3.497
|View full text |Cite
|
Sign up to set email alerts
|

The need to belong: Desire for interpersonal attachments as a fundamental human motivation.

Abstract: A hypothesized need to form and maintain strong, stable interpersonal relationships is evaluated in light of the empirical literature. The need is for frequent, nonaversive interactions within an ongoing relational bond. Consistent with the belongingness hypothesis, people form social attachments readily under most conditions and resist the dissolution of existing bonds. Belongingness appears to have multiple and strong effects on emotional patterns and on cognitive processes. Lack of attachments is linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

427
11,913
15
428

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16,683 publications
(12,783 citation statements)
references
References 270 publications
427
11,913
15
428
Order By: Relevance
“…Rejection may have been more potent in these situations because participants were motivated to be valued and accepted by these people (Leary & Baumeister, 2000). Whereas rejection by peripheral persons, for whatever reason, may be upsetting, or disturbing, it may still have no impact on self-esteem, if the person's need for belonging have been adequately met by significant others (Baumeister & Leary, 1995). shown that the level of integration of one's identity impacts social cognition (BenetMartinez et al, 2002;Haritatos & BenetMartinez, 2002). These studies have shown that Asian Americans presented with a prime for Asian culture will respond to a culturally discerning task in a manner congruent with the Asian prime, if they have an integrated identity.…”
Section: Discussionmentioning
confidence: 99%
“…Rejection may have been more potent in these situations because participants were motivated to be valued and accepted by these people (Leary & Baumeister, 2000). Whereas rejection by peripheral persons, for whatever reason, may be upsetting, or disturbing, it may still have no impact on self-esteem, if the person's need for belonging have been adequately met by significant others (Baumeister & Leary, 1995). shown that the level of integration of one's identity impacts social cognition (BenetMartinez et al, 2002;Haritatos & BenetMartinez, 2002). These studies have shown that Asian Americans presented with a prime for Asian culture will respond to a culturally discerning task in a manner congruent with the Asian prime, if they have an integrated identity.…”
Section: Discussionmentioning
confidence: 99%
“…1 One area that has received relatively little research attention focuses on the quality of health care that heavy patients report receiving from their physicians. One might assume that physicians deliver a particularly strong dose of compassion, care, and responsiveness to their overweight patients, who suffer on medical dimensions, 2,3 social dimensions, [4][5][6] and overall well-being. [7][8][9] Similarly, physicians might be anticipated to view favorably and give quality treatment to overweight patients because, unlike the general population who tend to believe that weight is a completely controllable condition, 10 physicians have access to mounting research showing genetic and uncontrollable aspects of body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Living alone has been identified as a risk factor for thwarted belongingness, which occurs when the basic human need to belong is unmet (Van Orden et al, 2010). Baumeister and Leary (1995) proposed that people "have a pervasive drive to form and maintain…lasting, positive, and significant interpersonal relationships" (p. 1). These interpersonal relationships need to be frequent, positive, and stable (Baumeister and Leary, 1995).…”
mentioning
confidence: 99%
“…Baumeister and Leary (1995) proposed that people "have a pervasive drive to form and maintain…lasting, positive, and significant interpersonal relationships" (p. 1). These interpersonal relationships need to be frequent, positive, and stable (Baumeister and Leary, 1995). Others have proposed that people need a psychological sense of belonging for mental health (Hagerty et al, 1992).…”
mentioning
confidence: 99%